Ad unicum selected works of Gothic, Renaissance and Mannerist art from the National Heritage Institute, Czech Republic - Radostová, Šárka; Baštýřová, Hana; Gaudek, Tomáš 1980-; Krejčová, Magdalena 1972- (National Heritage Institute, 2020)
The publication deals with works of art from Gothic to Mannerism from the furnishings collection in the castles and chateaux under the administration of the National Heritage Institute (NHI) in the Czech Republic. The opening study introduces the issue of provenance research.The core of the collection was entrusted to the nowadays NHI following its expropriation after the Second World War. The aim of this book is to present selected paintings, carvings and other objects, in eighty elaborate and in-depth entries, with the emphasis on works of art significant for international research (Master of Třeboň Alterpiece, Tilman Riemenschneider, Hans Toman, Hans Brosamer, Benedetto Buglioni, Joachim Patinir, Jacob Seisenegger, Herri met de Bles, Mirabelo Cavalori, Bartholomeus Spranger, Jan Gossaert, Jacob Grimmer, Lucas, Gillis and Frederick van Valckenborch, Jacob de Backer, Dosso and Battista Dossi, Master IP, Gielis Panhedel etc.). The essays are accompanied by superb photographs, creating a unique art-historical resource.--publisher's description
Keywords: Kunst; Museum; Tschechien; Národní památkový ústav; mobiliární fondy / Česko; umělecké sbírky / Česko; zámecké obrazárny / Česko; evropské výtvarné umění / 14.-17. století; movable cultural monuments / Czechia; art collections / Czechia; chateau picture galleries / Czechia; European art / 14th-17th centuries; 14.-17. století; kolektivní monografie; katalogy; collective monographs; catalogs